Does money lead inflation in the euro area? - Sergio Nicoletti-Altimari (European Central Bank (ECB), 2001)
This paper investigates the properties of monetary and credit aggregates as indicators for future price developments in the euro area. The forecasting performance of models including indicators based on money and credit is assessed in a simulated out-of-sample forecasting exercise for forecast horizons varying from one quarter to three years ahead. The performance of these models is compared with that of models which include indicators based on financial markets, real activity, the labour market and various cost and price measures. The results support the idea that monetary and credit aggregates provide significant and independent information for future price developments in the euro area, especially at medium term horizons
Keywords: E31; E40; C32; 330